Usability of Assistive Technologies for the Learners with Hearing Impairment in Federal College of Education - Florence Olutunu Daramola (Indonesian Journal of Community and Special Needs Education, 2022)
The study was geared towards the usability of assistive technologies for learners with hearing impairment. Descriptive research of the Survey design was adopted. The sample comprised of one hundred and ten hearing impaired students of Federal College of Education (Special) Oyo. An adopted checklist and a structured questionnaire were utilized in collecting data while simple percentages, mean standard deviation, and t-test was used to analyze the data collected. The results of the study indicated that assistive technologies in FCE (SP) Oyo are generally available and functional; the use of assistive technologies among the learners with hearing impairment in FCE (SP) Oyo is high. Also, the result indicated that learners with hearing impairment in FCE (SP) Oyo have a positive attitude towards the use of assistive technologies.  There was no significant difference between male and female learners with hearing impairment in the use of assistive technologies in FCE (SP) Oyo. It was recommended among others that learners with hearing impairment should be encouraged to adopt the ultimate use of assistive technologies.